An Approach to the Carboniferous-Early Permian Stratigraphy, Paleontology, Paleogeography And Paleoclimatology of the Calingasta-Uspallata Subbasin (Western Argentina) and Tepuel-Genoa Basin (Patagonia), Argentina: A Fieldguide - Taboada, Arturo Cesar (2009)
The purpose of this contribution is to present to all Upper Paleozoic workers an adaptation of the fieldguide used in the “Second International Symposium and Field Workshop on the Carboniferous-Early Permian Stratigraphy, Paleontology, Paleogeography and Paleoclimatology of the Calingasta-Uspallata Subbasin (western Argentina) and TepuelGenoa Basin (Patagonia), Argentina”. The symposium took place during February 16 and March 2, 2009 in Argentina.